SUSTAINABLE LIBRARY PRACTICES FOR THE 21ST CENTURY - Kedar, Manohar Baburao; Kedar, Neeta Manohar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the 21st century, libraries are not only information centers but also pivotal agents of sustainability. As global attention intensifies on climate change, social equity, and responsible resource use, libraries must adopt sustainable practices that align with environmental, economic, and social sustainability goals. This article explores the concept of sustainability in libraries, outlines practical strategies, and highlights best practices from around the world, offering a blueprint for libraries aiming to make meaningful contributions to sustainable development.